FAKTOR-FAKTOR YANG MEMPENGARUHI DANA MENGANGGUR (IDLE CASH) BERDASARKAN PERSEPSI PENGAMBIL KEPUTUSAN Studi Kasus di Kabupaten Sleman Tahun 2010 - , Tin Ibriz Fana, S.E.; , Prof. Dr. Samsubar Saleh, M.Soc.Sc., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main purposes of public institution, in this case local government, are to provide the best possible service to the community as well as to provide public infrastructure that can support community activities to improve their welfare by empowering existing cash to immediately meet the needs of the public. However, there are several variables causing the cash unable to be immediately distributed, in turn making the funds idle. The purpose of this study is to find out the perception of decision makers on five factors affecting idle cash in Sleman Regency in 2010. The five factors are regulatory system, highly competent and committed human resources, planning and budgeting, budget realization, control, and evaluation. The data used were secondary and primary data through questionnaires for respondentsâ perceptions of idle cash. The primary data were collected from 46 respondents from 46 Local Apparatus Work Units (Satuan Kerja Perangkat DaerahâSKPD) in Government of Sleman Regency, which was measured using a Likert scale. A product moment validity test and Cronbach alpha reliability test were done for the feasibility of the instrument. The perception of respondents was calculated using the rating scale. Results of the analysis indicate that the respondentsâ perceptions of four variables were high enough: regulatory systems (71.37 percent), highly competent and committed human resources (76.43 percent), planning and budgeting (75.54 percent), and control and evaluation (77.89 percent). The variable with the highest level of perception was budget realization (84.78 percent).